A Study of Indications, Clinical Applications, and Effects of Therapeutic Phlebotomy at a Tertiary Care Hospital Navi Mumbai - Sonal Suresh Gupta; Shweta Wasudeo Dhote; Shubhangi Lad; Damayanti Radhashyam Dey (Global Journal of Transfusion Medicine)
Background and Objectives: The removal of blood from the body is known as phlebotomy, venesection, or bloodletting. Therapeutic phlebotomy is the preferred treatment for blood disorders where removing red blood cells or serum iron is the most effective way to manage symptoms and complications. In current medical practice, therapeutic phlebotomy is a clinically-supervised intervention for diseases such as polycythemia vera, hemochromatosis, porphyria cutanea tarda, nonalcoholic fatty liver disease, and sickle cell crisis. The aim of this study was to analyze the indications for therapeutic phlebotomy and its effects on hematocrit and hemoglobin. Methods: A retrospective study spanning 5 years was conducted in the department of immunohematology and blood transfusion, collecting patient clinical details, including name, age, gender, symptoms, and diagnosis. Results: A progressive decline in hemoglobin and hematocrit levels was noted in patients undergoing different numbers of therapeutic phlebotomy sessions. Hematocrit reduction was significantly greater in patients with four or more sessions (P < 0.001), while hemoglobin levels decreased more significantly after three sessions (P < 0.001). In conclusion, it required more phlebotomy cycles to reduce hematocrit compared to hemoglobin. Conclusion: Therapeutic phlebotomy is an essential part of the treatment of various diseases, especially those associated with secondary polycythemia. It is safe and cost-effective that should also be considered for use as adjunctive therapy.